Salivary Cortisol Does Not Correlate with Metabolic Syndrome Markers or Subjective Stress in Overweight Children - Strait, Robert B. (J Child Obes, 2018)
OBJECTIVE: Being overweight is a risk factor for metabolic syndrome in children, but not all overweight children develop metabolic syndrome. Cortisol excess from chronic psychological stress has been proposed as an independent risk factor for metabolic syndrome in this already at-risk population. The present study assesses the relationship of biochemical and body composition radiographic markers of metabolic syndrome to salivary cortisol and self-report of chronic psychological stress in a cohort of overweight children. METHODS: This cross-sectional study took place in a multi-disciplinary pediatric obesity clinic at a tertiary care hospital, and involved fifteen children with BMI at or above the 85(th) percentile for age and sex, 10 of whom provided salivary cortisol samples. The main outcomes measured were salivary bedtime cortisol, first-waking cortisol, and cortisol awakening response (CAR–the rise in cortisol in the first half hour after waking); fasting serum triglycerides, HDL cholesterol, glucose and insulin for HOMA-IR; the ratio of abdominal fat to total body fat by DXA scan; and scores of validated stress and bullying questionnaires (PANAS-C, PSS, and SEC-Q). RESULTS: In this pilot study, no correlation was found between salivary cortisol measures and questionnaire scores of subjective stress or bullying, and no correlation was found between any of these measures and markers of metabolic syndrome (dyslipidemia, insulin resistance, increased abdominal fat). CONCLUSIONS: These results suggest that measures of psychological stress, whether biochemical or subjective, do not appear to predict risk of metabolic syndrome in overweight children. While ease of collection and demonstrated utility both in detection of pediatric Cushing disease and in adult psychological research make salivary cortisol assessment an attractive clinical tool, further investigation into the value of salivary measures in pediatric stress research is needed.